Enhancing the efficiency and effectiveness of maize breeding program through the EBS Platform - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2022)
EBS (Enterprise Breeding System) platform is a centralized workflow based system for maize breeders. It has a lot of functionality that will help improve the efficiency and effectiveness of maize breeding program. It is also a standardized system that will be used to measure genetic gain in Realtime.